Improvement of ionospheric sounding modes in the incoherent scatter technique - Emelyanov, L.Ya.; Pulyayev, V.O.; Kuzmenko, N.O.; Dziubanov, D.A. (Radiotekhnika, 2025)
Improvement of the modes of high-frequency radio waves pulsed radiation, reception and processing of received signals incoherently scattered by ionospheric plasma, implemented using incoherent scatter radars intended for remote sensing of near-Earth space are exemplified. An analysis of some modes of radio pulse sounding was carried out, namely the mode using a long radio pulse intended for the upper ionosphere study, and a mode for the lower ionosphere study, when the sounding signal was emitted in the form of two short elements, the distance between which varied depending on the radar scan number. The advantages and disadvantages of these modes are shown. Options for using radio pulses of a more complex structure are proposed due to the optimal coding of a larger number of elements taking into account the nature of scattering in the ionospheric plasma. The results of the search for multi-element coded signals for the study of the lower and upper altitude ranges are presented, providing the calculation of the ordinates of the scattered signal autocorrelation function with high resolution both in space and time. The hardware implementation of sounding modes using these signals is presented. In particular, a block diagram of the incoherent scatter radar is presented for working with signals of opposite circular polarizations, which uses for this purpose-controlled phase shifters of the transmitter excitation system, orthogonal antenna vibrators and ring bridge of the receiving-feeder path. The change in the parameters of the high-frequency filling of the sounding radio signal is carried out according to the signals of the radar control system. In general, this makes it possible to transmit and receive signals with various coding options for their elements, most suitable for specific conditions, and to use modes in which the direction of circular rotation of the plane of polarization of the radio wave changes. A multi-channel computing device is proposed for calculating the autocorrelation function of the incoherent scatter signal when using such coded signals.